DIAGNOSA PENYAKIT BELL’S PALSY MENGGUNAKAN ALGORITMA FINITE STATE AUTOMATA - Fatiha, Zulfati Dinul; Krisnandi, Dwi; Putra, Jordy Lasmana; Novitasari, Hafifah Bella; Gata, Windu (Fakultas Teknik, Universitas Tadulako, 2021)
Bell's Palsy is a neurological disorder that causes paralysis of the face. Delayed treatment will increase the risk of permanent disability and other problems such as psychological problems. Lack of knowledge, cost constraints, and limited places for consultations caused low public awareness for diagnosis. A diagnosis system is needed for Bell's Palsy disease, so recovery can be faster and reduce negative effects. The system design will use the Finite State Automata Algorithm to describe the pattern so that the program is more structured and directed. The design is expected to help create an early diagnosis system that is useful for the community and can be accessed easily, quickly, and efficiently.